The prevalence of ortorexia nervosa among university healthy students: A descriptive review (Research, Society and Development, 2021)
The expression “Orthorexia Nervosa” (ON) is related to “orthos”, an indicative of correct, and “o-rexis”, of appetite, being defined like an obsession with healthy eating habit. The most affected public is the adolescents and young female adults, which presents as consequences of ON several social and psychological damages. The aim of this study was to describe the prevalence of tendency to ON in healthy university students through a descriptive review. The research was carried out on the bases Pubmed, Scielo, Bireme using the key words (orthorexia nervosa) AND (university students) OR (eating behavior); (eating disorder) AND (university students) OR (eating behavior); The Search resulted in 119 publications and after screening, 11 studies were selected. Regarding the publications where the following data were extracted: title of the study, year of publication, authors, objective, sample and main results. Most of the selected studies addressed students in Nutrition course, as they are believed to be a risk group due to their knowledge relative to healthy eating, a characteristic not observed in others populations subgroups, and used the ORTO-15 questionnaire to collect data about food. The average percentage of presence of risk behaviors for ON was approximately 85,31%. The results showed a higher prevalence of risk behaviors among women. It was observed, therefore, that students showed a high frequency of risk behaviors for the development of ON, making them susceptible to the social, psychological and health consequences motivated by this disorder.